Diagnosis of out-of-hospital cardiac arrest by emergency medical dispatch: A diagnostic systematic review. (February 2021) - Drennan, Ian R.; Geri, Guillaume; Brooks, Steve; Couper, Keith; Hatanaka, Tetsuo; Kudenchuk, Peter; Olasveengen, Theresa; Pellegrino, Jeffrey; Schexnayder, Stephen M.; Morley, Peter; ,; ,; et al.
Abstract: Introduction: Cardiac arrest is a time-sensitive condition requiring urgent intervention. Prompt and accurate recognition of cardiac arrest by emergency medical dispatchers at the time of the emergency call is a critical early step in cardiac arrest management allowing for initiation of dispatcher-assisted bystander CPR and appropriate and timely emergency response. The overall accuracy of dispatchers in recognizing cardiac arrest is not known. It is also not known if there are specific call characteristics that impact the ability to recognize cardiac arrest. Methods: We performed a systematic review to examine dispatcher recognition of cardiac arrest as well as to identify call characteristics that may affect their ability to recognize cardiac arrest at the time of emergency call. We searched electronic databases for terms related to "emergency medical dispatcher", "cardiac arrest", and "diagnosis", among others, with a focus on studies that allowed for calculating diagnostic test characteristics (e.g. sensitivity and specificity). The review was consistent with Grading of Recommendations, Assessment, Development and Evaluation (GRADE) method for evidence evaluation. Results: We screened 2520 article titles, resulting in 47 studies included in this review. There was significant heterogeneity between studies with a high risk of bias in 18 of the 47 which precluded performing meta-analyses. The reported sensitivities for cardiac arrest recognition ranged from 0.46 to 0.98 whereas specificities ranged from 0.32 to 1.00. There were no obvious differences in diagnostic accuracy between different dispatching criteria/algorithms or with the level of education of dispatchers. Conclusion: The sensitivity and specificity of cardiac arrest recognition at the time of emergency call varied across dispatch centres and did not appear to differ by dispatch algorithm/criteria used or education of the dispatcher, although comparisons were hampered by heterogeneity across studies. Future efforts should focus on ways to improve sensitivity of cardiac arrest recognition to optimize patient care and ensure appropriate and timely resource utilization.